2011
DOI: 10.1002/rcm.4918
|View full text |Cite
|
Sign up to set email alerts
|

Electron ionization mass spectra of alkylated sulfabenzamides

Abstract: Mono-, di- and trialkyl derivatives of 'sulfabenzamide' (N-4-aminophenylsulfonylbenzamide) have been prepared and their electron ionization (EI) mass spectra examined. It is found that the fragmentation of N-alkylsulfabenzamides (alkyl = CH(3) to n-C(5)H(11)) proceeds via a very specific rearrangement process. The proposed mechanism involves an intermediate formation of distonic molecular ions, and the driving force for this process is the formation of stable N-alkylphenylcyanide cations [R-N(+)≡CC(6)H(5)]. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Thus, a high-intensity peak of N-tolylacetonitrile cation at m/z 186 (55%) is observed in the Oxygen rearrangements leading to nitrilium cations have been observed previously for other compounds as well. Thus, N-alkyl-C-phenylnitrilium cations are the base peaks in the EI spectra of N-alkylsulfabenzamides; 34 it was established that the mechanism involves an ipso attack of the amide oxygen and further fragmentation to the thermodynamically or kinetically favored products. 36 Type a ions were observed in the EI spectra of N-methyl-N-TFA-amphetamines and a four-centered mechanism of oxygen migration has been suggested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a high-intensity peak of N-tolylacetonitrile cation at m/z 186 (55%) is observed in the Oxygen rearrangements leading to nitrilium cations have been observed previously for other compounds as well. Thus, N-alkyl-C-phenylnitrilium cations are the base peaks in the EI spectra of N-alkylsulfabenzamides; 34 it was established that the mechanism involves an ipso attack of the amide oxygen and further fragmentation to the thermodynamically or kinetically favored products. 36 Type a ions were observed in the EI spectra of N-methyl-N-TFA-amphetamines and a four-centered mechanism of oxygen migration has been suggested.…”
Section: Resultsmentioning
confidence: 99%
“…EI mass spectra were recorded on GC-MS systems with quadrupole analyzers (ionization energy 70 eV and ion source temperature 230°C), as previously described. 34 Separation was achieved on a fused silica capillary column (30 m, 0.25 mm internal diameter, and nonpolar stationary liquid phase of polymethylsiloxane + 5% phenyl groups) with programmed oven temperature from 60°C to 270°C at a rate of 5 C min -1 ; the injection temperature was 230°C. GC tandem mass spectrometry (MS/MS) data were obtained at 2, 5, 10, and 17 eV collision energies on systems with quadrupole analyzers using nitrogen as the collision-induced dissociation gas.…”
Section: Instrumentationmentioning
confidence: 99%
“…One example was reported recently, in which alkylation gave an unexpected and puzzling result . When the amidic nitrogen is not alkylated, the dominant base peak in the mass spectra of simple sulfabenzamide derivatives is the corresponding phenol radical cation, as expected from established fragmentation rules for sulfones. In particular, Meyerson and co‐workers described a sulfone‐sulfinate rearrangement giving rise to arylsulfoxyl and aryloxyl ions.…”
Section: Methodsmentioning
confidence: 94%
“…When followed by a hydrogen migration, this corresponds to the mechanism shown in Scheme for R 1 = H. However, amidic N ‐alkylation (R 1 = alkyl) suppresses the phenol radical cation completely. Instead, the base peak in the mass spectrum is a closed‐shell alkyl benzonitrilium ion . This indicates that the amidic oxygen atom is migrating.…”
Section: Methodsmentioning
confidence: 99%
“…and a molecule RCN, leading to very intense peaks in the spectra. 36 In the other work, 37 mono-, di-and trialkyl derivatives of "sulfabenzamide" (N-4-aminophenylsulfonylbenzamide) have been prepared and their EI mass spectra examined. It was found that the fragmentation of N-alkylsulfabenzamides (alkyl = CH 3 to n-C 5 H 11 ) proceeds via a very specific rearrangement process giving rise to stable N-alkylphenylcyanide cations [RN + = CC 6 H 5 ].…”
Section: Organic Chemistrymentioning
confidence: 99%